An overview of current technologies and emerging trends in factory automation. Issue 15 (29th August 2019) - Dotoli, Mariagrazia; Fay, Alexander; Miśkowicz, Marek; Seatzu, Carla
Abstract : In this paper we provide an overview of recent theoretical approaches and technologies that respond to the fundamental challenges of modern factory automation. We classify these major methods and technologies into several groups and, for seven of them - namely: vertical integration of factory automation systems; distributed and decentralised control, smart sensors and actuators in factories; networked control systems and wireless sensors and actuators; autonomy and self-organisation of factories; advanced sensing for factory automation; semantic models of factories; engineering methods of factory automation systems - we report recent research contributions and formulate open technical problems in the domain of modern factory automation.